1994
DOI: 10.1302/0301-620x.76b1.8300674
|View full text |Cite
|
Sign up to set email alerts
|

Youth is a risk factor for stress fracture. A study of 783 infantry recruits

Abstract: We report a prospective study of783 male Israeli recruits aged from 17 to 26 years. The risk of stress fracture was inversely proportional to age on both univariate and multivariate analysis. Each year of increase of age above 17 years reduced the risk of stress fracture by 28%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 0 publications
1
49
1
4
Order By: Relevance
“…Younger age as a risk factor for stress fractures has been previously shown in the Israeli military. [17] Their findings showed that as age increased from 17 years through to 26 years, bony injury risk decreased by 28% per year. The findings in this present study are consistent with this trend, although it is difficult to compare the two populations, with only 3.3% (26 out of 796) of the military population over the age of 19 years, whereas this study's population was comprised of athletes of whom 98% were above the age of 19 years.…”
Section: Discussionmentioning
confidence: 98%
“…Younger age as a risk factor for stress fractures has been previously shown in the Israeli military. [17] Their findings showed that as age increased from 17 years through to 26 years, bony injury risk decreased by 28% per year. The findings in this present study are consistent with this trend, although it is difficult to compare the two populations, with only 3.3% (26 out of 796) of the military population over the age of 19 years, whereas this study's population was comprised of athletes of whom 98% were above the age of 19 years.…”
Section: Discussionmentioning
confidence: 98%
“…One-stage long-stem TKA restores limb alignment and facilitates fracture healing, with excellent outcome. [1][2][3] and rheumatoid arthritis, 4,5 osteoarthritis, [6][7][8] osteoporosis, 1 post-traumatic deformity, 9 deformed degenerate knees, 4,10 Paget's disease, 11 pyrophosphate arthropathy, 12 and knee arthroplasty (unicondylar and navigated) [13][14][15][16] in elderly people. Stress fractures are usually treated by rest and/or casting 6,10,17 and rarely surgery.…”
mentioning
confidence: 99%
“…Small stature, younger age, Caucasian, and female gender have been reported as risk factors for pubic ramus fractures in the general population [1,15,20,22]. Similarly, the majority of patients who sustained pubic fractures after PAO fit these criteria.…”
Section: Discussionmentioning
confidence: 93%